2011
DOI: 10.1016/j.aju.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Interposition of dartos flaps to prevent fistula after tubularized incised-plate repair of hypospadias

Abstract: Objective: To evaluate the effect of urethral coverage by a single- or double-layered dorsal dartos flap after tubularized incised-plate (TIP) repair of hypospadias on fistula formation.Patients and methods: In this retrospective study we evaluated sequential patients with hypospadias who underwent TIP urethroplasty with a dorsal dartos interpositional flap between April 2008 and December 2009. We reviewed their medical records for the site of hypospadias, previous hypospadias repair, single- or double-layered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…Djordjevic et al [25, 26] also reported no fistula formation with single-dartos flaps. However, other researchers did not get similar results and reported fistula rates of 13% [27] and 26% [22] using single-dartos flaps. As mentioned above, the most common complication of hypospadias repair is fistula, which can be prevented by placing a barrier layer between the neourethra and the overlying glans and shaft skin closures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Djordjevic et al [25, 26] also reported no fistula formation with single-dartos flaps. However, other researchers did not get similar results and reported fistula rates of 13% [27] and 26% [22] using single-dartos flaps. As mentioned above, the most common complication of hypospadias repair is fistula, which can be prevented by placing a barrier layer between the neourethra and the overlying glans and shaft skin closures.…”
Section: Discussionmentioning
confidence: 97%
“…Appignani et al [20] reported that the double-dartos flaps had significantly lower rates of fistula formation. Most studies conducted on the issue, including those by Yigiter et al [21], Elsayed et al [22], and Erol et al [23], also indicated lower rates of fistula formation using double-dartos flaps, but the difference was not statistically significant. Bertozzi et al [24] performed a multicenter review of 394 cases of hypospadias repair covered with double-dartos flaps and reported fistulae in only four cases [1.01%].…”
Section: Discussionmentioning
confidence: 99%
“…3,[14][15][16][17][18][19] On the other hand, Elsayed et al reported no significant difference in subsequent Urethrocutaneous Fistula (UCF) between a doublelayered dorsal dartos flap and single layer for covering the urethra as a part of TIP urethroplasty for repairing hypospadias. 20 Spongiosal tissue has been used by many surgeons to prevent fistula and other complications from its introduction in 2000 by Beaudoin 7 and Yerkes. 21 Yerkes et al noticed no fistula in any of the patients of spongioplasty in a different urethral repair technique.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the fistula rate was higher among urethroplasties covered with a single layer (8%) than with a double layer (none), although the difference was not statistically significant ( P = 0.1). Many other studies have compared a single and double dartos interposition flap after TIP urethroplasty ( Table 2 ) [15–21] .…”
Section: Discussionmentioning
confidence: 99%